2018
DOI: 10.1080/1059924x.2017.1387634
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease and Health Risk Behaviors Among Rural Agricultural Workforce in Queensland

Abstract: This method of investigation both raises awareness in the community and identifies health risks for further management in a group that has otherwise been poorly defined. Resident agricultural workers have different health risks and behaviors, though psychological distress appears to be borne across these communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This is another limitation of using a retrospective design, nonetheless, delay in management is a clear factor in agricultural injuries that warrants further investigation of contribution to health outcomes and education in evacuation planning for farmers. In addition to these physical factors, psychological distress may be another factor associated with the incidence of agricultural injuries and should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is another limitation of using a retrospective design, nonetheless, delay in management is a clear factor in agricultural injuries that warrants further investigation of contribution to health outcomes and education in evacuation planning for farmers. In addition to these physical factors, psychological distress may be another factor associated with the incidence of agricultural injuries and should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of the World Health Organization (WHO), health is affected by such factors: health behavior, environment, genetic and health services, and health behavior accounts for the largest proportion, more than 60% [3]. And studies [4][5] have even shown that some health risk behaviors were closely related to the occurrence and deterioration of diseases, especially smoking, excessive drinking, lack of exercise, etc. According to the Chinese government's report on chronic diseases, diseases caused by health risk behaviors are particularly prevalent in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of inequalities varies significantly within Europe, and there are a number of models that attempt to capture this variation and embrace the numerous determinants of inequalities [14][15][16][17]. One of the determinants is rural vs. urban residence-it has been demonstrated that rural inhabitants have limited access to health care [18][19][20][21][22] and attend specialist care less often than city dwellers [20,23]. Rural populations have higher prevalence of certain behavioural risk factors [18,19,24,25] and tend to be more difficult to reach with health-promoting messages [18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the determinants is rural vs. urban residence-it has been demonstrated that rural inhabitants have limited access to health care [18][19][20][21][22] and attend specialist care less often than city dwellers [20,23]. Rural populations have higher prevalence of certain behavioural risk factors [18,19,24,25] and tend to be more difficult to reach with health-promoting messages [18]. They often face systemically limited access to preventative healthcare.…”
Section: Introductionmentioning
confidence: 99%